Analysis of the Effect of DTPB on User Intention to Keep Using the Flip Application - Adilah Purnamasari; Fiqi Pranastara; Iftina Salya Rosa; Dwiza Riana; Sri Hadianti (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Many Community needs have to be supported by the novelty of the technology. It makes more and more developers innovate in making an application. One form of technological novelty is digital payment applications. Currently, there are many digital payment applications in Indonesia, one of them is Flip. id application. To compete with other digital payment applications, Flip needs to be constantly developed. Therefore, the main purpose of this research is to find out how much the level of user acceptance of the application and what factors can affect the user's intention to continue using the Flip application in the long term. This user intention analysis will be carried out using the Decomposed Theory of Planned Behavior method, which will then be tested using the SmartPLS software. Based on the research results, it is known that the attitude variable and perceived behavioral control influence the intention to use or the user's intention to continue using the Flip application in the long term. The attitude variable itself is supported by other variables such as perceived ease of use, perceived usefulness, and playfulness, while the perceived behavioral control variable is supported by the resource facilitating condition, self-efficacy, and technology facilitating condition variables. Other variables that do not affect the intention to use variables include compatibility, subject norm, superior's influence, and peer influence variables.